2017
DOI: 10.1021/jacs.7b03878
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Assembly of Peptide Amphiphile via Noncovalent-to-Covalent Bond Conversion

Abstract: Controlling the number of monomers in a supramolecular polymer has been a great challenge in programmable self-assembly of organic molecules. One approach has been to make use of frustrated growth of the supramolecular assembly by tuning the balance of attractive and repulsive intermolecular forces. We report here on the use of covalent bond formation among monomers, compensating for intermolecular electrostatic repulsion, as a mechanism to control the length of a supramolecular nanofiber formed by self-assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 40 publications
2
67
0
Order By: Relevance
“…Moreover, this work illustrates a new approach for switching the conformations of peptides and offers new insights for understanding the functions of inherent disorder regions of proteins, a subject with increasing importance in chemistry and biomedicine. Being easily accessible via solid phase synthesis, peptides are becoming important building blocks for generating supramolecular assemblies for a wide range of applications such as antibacterial agent, [18] self-assembly with non-covalent interaction, [19] conjugating with anticancer drug, [20] and sequence control for generating melanin-like color. [21] Therefore, the use of enzyme reaction for controlling the secondary structure of peptides will contribute to design more sophisticated and intelligent soft biomaterials for a wide range of applications.…”
mentioning
confidence: 99%
“…Moreover, this work illustrates a new approach for switching the conformations of peptides and offers new insights for understanding the functions of inherent disorder regions of proteins, a subject with increasing importance in chemistry and biomedicine. Being easily accessible via solid phase synthesis, peptides are becoming important building blocks for generating supramolecular assemblies for a wide range of applications such as antibacterial agent, [18] self-assembly with non-covalent interaction, [19] conjugating with anticancer drug, [20] and sequence control for generating melanin-like color. [21] Therefore, the use of enzyme reaction for controlling the secondary structure of peptides will contribute to design more sophisticated and intelligent soft biomaterials for a wide range of applications.…”
mentioning
confidence: 99%
“…[42,43] The growth of amyloid fibrils can take place on either end, [44] and the fibrillation of peptide assembly sometimes requires acidic conditions [45][46][47] or other stimuli. [54][55][56] In one peptide amphiphile, an amino acid group is covalently linked with a hydrophobic chain (e.g., alkyl chain). [49][50][51][52] It is worth noting that the inner hollow channel of tube-like amyloids can be used for "casting" metal nanowires.…”
Section: Self-assembled Small Biomoleculementioning
confidence: 99%
“…Peptides or proteins are among the most fascinating architectures to precisely control chirality via self‐assembly . As a consequence of amino acid chirality, an entire hierarchy of self‐assembling macromolecular architectures is accessible, with tapes as the most primitive form: fibrils, fibers, and ribbons . Pioneering studies by Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Peptides or proteins are among the most fascinating architectures to precisely control chirality via self-assembly [9]. As a consequence of amino acid chirality, an entire hierarchy of self-assembling macromolecular architectures is accessible, with tapes as the most primitive form: fibrils, fibers, and ribbons [10][11][12][13][14]. Pioneering studies by Zhang et al and others demonstrated that a group of short surfactant-like peptides with the similar diameter as phospholipids or phosphatidylcholine can selfassemble into ordered nanostructures with intriguing chiral properties [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%